Role of the PLDLS-Binding Cleft Region of CtBP1 in Recruitment of Core and Auxiliary Components of the Corepressor Complex - Kuppuswamy, M. (American Society for Microbiology (ASM), 2008)
C-terminal binding protein (CtBP) family proteins CtBP1 and CtBP2 are highly homologous transcriptional corepressors and are recruited by a large number of transcription factors to mediate sequence-specific transcriptional repression. In addition to DNA-binding repressors, the nuclear protein complex of CtBP1 consists of enzymatic constituents such as histone deacetylases (HDAC1/2), histone methyl transferases (HMTases; G9a and GLP), and the lysine-specific demethylase (LSD1). Additionally, CtBPs also recruit the components of the sumoylation machinery. The CtBPs contain two different unique structural elements, a hydrophobic cleft, with which factors that contain motifs related to the E1A PLDLS motif bind, and a surface groove that binds with factors containing motifs related to the sequence RRTGXPPXL (RRT motif). By structure-based functional dissection of CtBP1, we show that the PLDLS-binding cleft region functions as the primary recruitment center for DNA-binding factors and for the core and auxiliary enzymatic constituents of the CtBP1 corepressor complex. We identify HDAC1/2, CoREST/LSD1, and Ubc9 (E2) as the core constituents of the CtBP1 complex, and these components interact with the PLDLS cleft region through non-PLDLS interactions. Among the CtBP core constituents, HDACs contribute predominantly to the repression activity of CtBP1. The auxiliary components include an HMTase complex (G9a/Wiz/CDYL) and two SUMO E3 ligases, HPC2 and PIAS1. The interaction of auxiliary components with CtBP1 is excluded by PLDLS (E1A)-mediated interactions. Although monomeric CtBP1 is proficient in the recruiting of both core and auxiliary components, NAD(H)-dependent dimerization is required for transcriptional repression. We also provide evidence that CtBP1 functions as a platform for sumoylation of cofactors.